2013
DOI: 10.1021/jf4016834
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Anticancer Compounds Se-Methylselenocysteine and Glucosinolates in Se-Biofortified Broccoli (Brassica oleracea L. var. italica) Sprouts and Florets

Abstract: Broccoli (Brassica oleracea L. var. italica) is a rich source of chemopreventive compounds. Here, we evaluated and compared the effect of selenium (Se) treatment on the accumulation of anticancer compounds Se-methylselenocysteine (SeMSCys) and glucosinolates in broccoli sprouts and florets. Total Se and SeMSCys content in sprouts increased concomitantly with increasing Se doses. Selenate was superior to selenite in inducing total Se accumulation, but selenite is equally effective as selenate in promoting SeMSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 43 publications
3
54
1
3
Order By: Relevance
“…In particular, selenate treatment increased the GSL content by 15.2% compared to the control. Previous studies reported that the total GSL content is minimally affected by selenate treatment in broccoli sprouts and mature broccoli (25 and 100 lmol/L) (Avila et al, 2013;Sepúlveda, Barrientos, Mahn, & Moenne, 2013). In the present study, the total GSL content was not affected after Se fertilization in cultivars FL60 and SL120, agreeing with previously reported values.…”
Section: Effects Of Control Selenite and Selenate Treatments On The supporting
confidence: 92%
See 1 more Smart Citation
“…In particular, selenate treatment increased the GSL content by 15.2% compared to the control. Previous studies reported that the total GSL content is minimally affected by selenate treatment in broccoli sprouts and mature broccoli (25 and 100 lmol/L) (Avila et al, 2013;Sepúlveda, Barrientos, Mahn, & Moenne, 2013). In the present study, the total GSL content was not affected after Se fertilization in cultivars FL60 and SL120, agreeing with previously reported values.…”
Section: Effects Of Control Selenite and Selenate Treatments On The supporting
confidence: 92%
“…Knowing that broccoli accumulates Se and S, 100 lmol/L selenite (Na 2 SeO 3 ) and 100 lmol/L selenate (Na 2 SeO 4 ) were deliberately selected as suitable concentrations which could result in substantial Se accumulation (Avila et al, 2013). In the present study, the total Se content was similar between the three cultivars after the different treatments (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…; Ávila et al . ). Broccoli sprouts are a good source of vitamin C, vitamin E, folic acid, dietary fibre, minerals, glucosinolates and phenols (Zielinski et al .…”
Section: Introductionmentioning
confidence: 97%
“…Broccoli also contains anthocyanins, which are members of the colored flavonoid class, and are considered multifunctional components of foods due to their antioxidant activity (Moreno et al 2010). A diet rich in cruciferous vegetables (e.g., cabbage, broccoli, cauliflower) is associated to a reduced risk of several human cancers (Gullett et al 2010;Avila et al 2013). Broccoli sprouts are a good source of vitamin C, vitamin E, folic acid, dietary fibre, minerals, glucosinolates and phenols (Zielinski et al 2005;P erez-Balibrea et al 2011;Jang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Também foi comprovado que brotos com 7 dias de idade expostos a concentração de 100 μM de selenato e de 75 μM e 100 μM de selenito apresentaram nítidos sintomas de toxicidade, como diminuição do crescimento da raiz e cotilédonos roxos. Além disso, estes sintomas foram mais expressivos nos brotos tratados com 100 μM de selenito, comprovando o maior potencial de toxicidade deste composto (ÁVILA et al, 2013).…”
Section: Selêniounclassified